The Impact of Peer Mentoring on Marketing Content Mastery. Issue 3 (1st September 2016) - Metcalf, Lynn E.; Neill, Stern; R. Simon, Lisa; Dobson, Sharon; Davis, Brennan
Abstract : This article describes and assesses a course design that uses peer mentors to facilitate a collaborative, hands-on learning experience in an introductory marketing course. Results demonstrate that peer mentoring increased content mastery and had a positive effect on students' perceptions of the learning experience. Peer marketing mentors, along with the faculty team, achieved success in providing a demanding and engaging learning environment that meets the needs of learners and equips them with content knowledge required of career-ready professionals. A step-by-step guide is provided to enable others to develop a similar experience for students in their institutions.